A SYSTEMATIC REVIEW ON THE ROLE OF POLICY INTERVENTIONS AND INSTITUTIONAL NETWORKS IN STRENGTHENING SME RESILIENCE - Najih, Mohammad Kholis Fajrun (Resilience of Small Medium Business, 2025)
Objective: This study also explores the role of policy interventions, institutional support, digital transformation, and networks in strengthening the resilience capacity of MSMEs.   Research Design & Methods: This study employed a Systematic Literature Review (SLR) approach by searching the academic databases Scopus, Web of Science, and ScienceDirect. Articles were selected based on strict inclusion criteria, focusing on peer-reviewed, academic publications relevant to MSME resilience. Analysis was conducted using thematic coding techniques and a synthesis matrix to examine interrelationships across studies. Findings: Four core components that significantly influence MSME resilience are Entrepreneurial Orientation, Networking, Digital Literacy, and Adaptability. Digital transformation has proven crucial for MSME survival, enabling adaptation to changing consumer patterns and increasing operational efficiency. Implications & Recommendations: These findings imply the need for a holistic and integrated policy approach, increased digital capacity, strengthened networks and ecosystems, and responsive and collaborative institutional support. Contribution & Value Added: This research broadens the understanding of MSME resilience by viewing it as a 'meta-capability' influenced by internal and external factors. Its contribution lies in strengthening the Resource-Based Theory (RBV) and institutional theory, and providing an evidence-based framework for policy reform and institutional strengthening to support MSMEs' long-term competitiveness and resilience